1982
DOI: 10.1115/1.3240859
|View full text |Cite
|
Sign up to set email alerts
|

Transient Characteristics of a Centrifugal Pump During Starting Period

Abstract: A theoretical and experimental study has been made on the transient characteristics of a centrifugal pump during its rapid acceleration from standstill to final speed. Instantaneous rotatinal speed, flow-rate, and total pressure rise are measured for various start-up schemes. Theoretical calculations for the prediction of transient characteristics are developed and compared with the corresponding experimental results. As the results of this study, it becomes clear that the impulsive pressure and the lag in cir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
53
1
1

Year Published

1996
1996
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(58 citation statements)
references
References 0 publications
3
53
1
1
Order By: Relevance
“…Similar to the results obtained by Tsukamoto [1] and Lefebvre [5], acceleration has a profound effect on the transient characteristics of a centrifugal pump. The transient performance has an obvious difference from the quasi-steady assumption results, and the peak value of head is markedly affected by the acceleration rate.…”
Section: Transient Performance Of Non-cavitation Pumpsupporting
confidence: 84%
See 1 more Smart Citation
“…Similar to the results obtained by Tsukamoto [1] and Lefebvre [5], acceleration has a profound effect on the transient characteristics of a centrifugal pump. The transient performance has an obvious difference from the quasi-steady assumption results, and the peak value of head is markedly affected by the acceleration rate.…”
Section: Transient Performance Of Non-cavitation Pumpsupporting
confidence: 84%
“…In recent years, more attention has been paid to the transient performance of pumps because of the growing engineering application needs. Tsukamoto et al [1,2] carried out an experimental and numerical study which investigated transient characteristics of a centrifugal pump during starting and stopping period. Results showed that the impulsive pressure and the lag in circulation formation around impeller vanes play dominant roles in the difference between dynamic and quasi-steady pump characteristics during the starting period.…”
Section: Introductionmentioning
confidence: 99%
“…Once the pump starts, the impeller rotational speed grows with time until the design value and the flow field inside the pump gradually enter a stable circulating state (Saito, 1982;Tsukamoto & Ohashi, 1982). The simulations were designed to study the transient solid-liquid flow fields but without factoring in the contributions due to the transient response of the impeller, in order to preserve reasonable computational efficiency.…”
Section: Transient Analysismentioning
confidence: 99%
“…This paper describes a procedure how to get the extended characteristic from measurement of fast pump deceleration in a simple hydraulic circuit. There is a lot of articles dealing with the problem of pump deceleration [2], [3] or acceleration [4], [5], [6], but authors found only little information about reconstruction of pump characteristic from measurement of this transients.…”
Section: Introductionmentioning
confidence: 99%